Influence of Fat Replacers on the Rheological, Tribological, and Aroma Release Properties of Reduced-Fat Emulsions - Schädle, Christopher; Sanahuja, Solange; Bader-Mittermaier, Stephanie (Foods, 2022)
Reduced-fat food products can help manage diet-related health issues, but consumers of-ten link them with poor sensory qualities. Thus, high-quality fat replacers are necessary to develop appealing reduced-fat products. A full-fat model emulsion was reduced in fat by replacing fat with either water, lactose, corn dextrin (CD), inulin, polydextrose, or microparticulated whey protein (MWP) as fat replacers. The effect of fat reduction and replacement, as well as the suitability of different types of fat replacers, were determined by analyzing fat droplet size distribution, composition, rheological and tribological properties, and the dynamic aroma release of six aroma compounds prevalent in cheese and other dairy products. None of the formulations revealed a considerable effect on droplet size distribution. MWP strongly increased the Kokini oral shear stress and viscosity, while CD exhibited similar values to the full-fat emulsion. All four fat replacers improved the lubricity of the reduced-fat samples. Butane-2,3-dione and 3-methylbutanoic acid were less affected by the changes in the formulation than butanoic acid, heptan-2-one, ethyl butanoate, and nonan-2-one. The aroma releases of the emulsions comprising MWP and CD were most similar to that of the full-fat emulsion. Therefore, CD was identified as a promising fat replacer for reducedfat emulsions.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Cheese aroma; Corn dextrin; Dietary fiber; Inulin; Lubricity; Microparticulated whey protein; Nutriose; Polydextrose; Proton-transfer-reaction mass spectrometry (PTR-MS); Simplesse